Barrett’s Esophagus and Cardiac Intestinal Metaplasia: Two Conditions within the Same Spectrum - Nicole White; Manal Gabril; Gershon Ejeckam; Maria Mathews; John Fardy; Fady Kamel; Jules Doré; George M Yousef (Canadian Journal of Gastroenterology)
BACKGROUND: Immunostaining for cytokeratin 7 (CK7) and cytokeratin 20 (CK20) has a characteristic pattern in Barrett’s esophagus (BE), but reports regarding its sensitivity and specificity are inconsistent. Intestinal metaplasia of the gastric cardia (CIM) is histologically similar to BE, but with no abnormal endoscopic findings.